Anesthesia management during aortic surgery: Preoperative patient assessment. Issue 3 (September 2016) - Mahlmann, Adrian; Weiss, Norbert
Abstract : Patients with aortic diseases have a high rate of cardiac, cerebrovascular, or pulmonary comorbidities. Open surgery or endovascular interventions of the aorta are associated with high perioperative cardiac risk. Simple scoring systems for preoperative risk stratification can be used to identify high-risk patients. In these patients, further diagnostic and therapeutic interventions are required to reduce perioperative morbidity and mortality. In contrast, low-risk patients can be identified, who may proceed to intervention without additional cardiopulmonary diagnostic testing. According to evidence-based recommendations in patients at risk, statin therapy should be initiated and beta blockers should be uptitrated preoperatively. Smoking cessation preoperatively reduces perioperative complications and should be encouraged in all patients.